Post-traumatic growth among Holocaust survivors: is it possible? - Schwartz, Kimberley (2015)
Within the world of psychological and mental health research, the field of post-traumatic growth has gained a louder voice, especially within the field of trauma and extreme trauma. This research paper shall explore the themes of post-traumatic growth amongst four Holocaust survivors who, out of all the camps and ghettos they were taken to, spent the most amount of time in Auschwitz-Birkenau. Using interpretative phenomenological approach (IPA), this paper identifies three domains of themes that emerged within all the narratives, which will be analysed further to identify their potential contribution to post-traumatic growth. This research will allow insight into the understanding of Holocaust trauma, and under what conditions it has thwarted or allowed post-traumatic growth to occur, seventy years later.